A survivor's education: women, violence, and the stories we don't tell - Neumeyer, Joy (PublicAffairs, 2024)
"In Berkeley, on a picturesque university campus in the springtime, a young woman is shoved backwards down a concrete stairway by her partner. This follows months of escalating violence, during which he slams her into walls, chokes her, pours beer on her, threatens to kill her, stalks her, promises to split her head open with a hammer. She ends the relationship, cuts off contact, flees to the other side of the country, and initiates a Title IX case against him at the university. She knows what has happened to her, what she has experienced and survived: abuse, manipulation, threats against her life, gaslighting. She knows she has lived through these trials. But others say, simply, that she hasn't-and that her boyfriend is the real victim. In this investigative memoir, historian and journalist Joy Neumeyer explores how violence against women is portrayed, perceived, defined, and adjudicated today, decades after the inception of Title IX. Interweaving the harrowing account of the abuse she experienced at the hands of her boyfriend when they were graduate students with those of other women who faced violence on campuses throughout history, Neumeyer offers a startling look at how little has changed in the years since Title IX was enacted, and uncovers its inherent flaws. She takes us through her own experience with the process, and reveals how in an effort to listen to survivors on campuses, the quasi-law, in reality, brings their experience into question. Deeply reported, nuanced and timely, A Survivor's Education demystifies Title IX while also examining how entangled storytelling is with abuse and power, and how we can balance narrative and evidence in our attempts to determine what "really happened.""-- Provided by publisher